Nietzsche’s Poethics: Poetry as a Way of Life in ’The Gay Science’ - Mills, Philip (Labyrinth, 2024)
The notion of poethics has been used to approach the way in which forms of language and forms of life are interdependent and to reveal the ethical dimension of poetics. However, the interaction must go both ways; there must not only be an ethical dimension to poetics, but also a poetic dimension to ethics. To what extent is ethics dependent on poetics? In this essay, I argue that Nietzsche’s life-affirming ethics can be understood only in this poethical framework. The specificity of Nietzsche’s ethics, and why it is so difficult to locate on the spectrum of ethical theories, lies in the fact that his ethics is a poetics. By focusing mainly on The Gay Science, I explore the interaction between ethics and poetics that lies at the heart of Nietzsche’s ethical thought. Both poetics and ethics involve the question of value, and a poetic ethics (a poethics) reveals that the creation of ethical value is something necessarily poetic. Nietzsche’s ethics of creation is not a mere theory, but a poetic way of life.